Presence of nanoplastics in rural and remote surface waters. (1st May 2022) - Materić, Dušan; Peacock, Mike; Dean, Joshua; Futter, Martyn; Maximov, Trofim; Moldan, Filip; Röckmann, Thomas; Holzinger, Rupert
Abstract: It is now established that microplastics are a pervasive presence in aquatic and terrestrial ecosystems. The same is assumed to be true for nanoplastics but data are lacking due to technical difficulties associated with sample analysis. Here, we measured nanoplastics in waterbodies at two contrasting sites: remote Siberian Arctic tundra and a forest landscape in southern Sweden. Nanoplastics were detected in all sampled Swedish lakes ( n = 7) and streams ( n = 4) (mean concentration = 563 µ g l −1 ) and four polymer types were identified (polyethylene, polyvinyl chloride (PVC), polypropylene, polyethylene terephthalate). In Siberia nanoplastics were detected in 7/12 sampled lakes, ponds and surface flooding, but only two polymer types were detected (PVC and polystyrene) and concentrations were lower (mean 51 µ g l −1 ). Based on back-calculation of air mass trajectories and particle dispersion, we infer that nanoplastics arrive at both sites by aerial deposition from local and regional sources. Our results suggest that nanoplastics may be a near-ubiquitous presence even in remote ecosystems.